Black executives today - Santos, Jefferson Monteiro Soares dos (Revista Extraprensa, 2017)
Review abaout the book Black executives: racism and diversity in the business world, Edusp, 2016, by Pedro Jaime de Coelho Júnior. This is a study of black voices about racism and diversity in the Brazilian business context.